Estrategias de cobranza y el cumplimiento de pago en los usuarios de Electro Oriente Iquitos año 2022 - Perez Pezo, Moises Noe (2023)
The research work on the local problem seeks through its development to determine the relationship between the collection strategies and the payment compliance of the Regional Public Services Company of Electricity of the East in 2022. It was executed based on the guidelines of the type applied, with relational purpose and procedural design adverse to the experiment, taking 383 users as population and sample, being the main informants of the current reality, recording their perception in a questionnaire. Coming to the conclusion that the collection strategy was developed in a medium way, because the communication was carried out mainly by telephone; the collection centers and the virtual payment platform were considered efficient, and adequate control of payments was carried out. As also, the level of payment compliance in users is medium, this is due to the fact that they are considered responsible in terms of their payment obligations, although occasionally it is required to cover other expenses far apart from the consumption of electrical energy; however, the economic income of the households can contribute to the fact that the electricity bills are paid on time. In short, there is a significant relationship between the variables, which was confirmed by a correlational factor (r=0.896), a positive and high factor, as well as a significance of (p=0.000).